Peningkatan Kreativitas Anak Usia 5-6 Tahun melalui Media Loose Part - Maulany, Fany; Rahman, Taopik; Qonita, Qonita (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2025)
Early childhood is a very important developmental stage in shaping children's character, thinking skills, and creativity, where children quickly respond to stimuli through learning experiences that are appropriate to their developmental stage. This study aims to improve the creativity of children aged 5–6 years through loose parts learning at Amal Sholeh Islamic Kindergarten in Tasikmalaya. The study used the Classroom Action Research (CAR) method model of Kemmis and McTaggart with four stages: Planning, Acting, Observing, and Reflecting. The research subjects were 17 children. Children's creativity was assessed based on five indicators: Fluency, Flexibility, Originality, Elaboration, and Sensitivity. The results of the study showed a significant increase in the planning and implementation of learning by teachers, as well as the development of children's creativity. In the pre-cycle stage, children's creativity abilities only achieved 15.8% (Undeveloped). In the first cycle, the teacher's ability in planning only got 78.5%, then the teacher's ability in implementation only got 52.7%. After improvement, in the second cycle, the teacher's ability in planning increased to 92.8%, for the teacher's ability in implementation also increased to 75%, then for the child's creativity ability increased to 51.1% (Developing According to Expectations). Until its peak in the third cycle, the teacher's ability in planning increased to 98.2%, and the teacher's ability in implementation increased to 94.4%, and for the child's creativity ability increased to 83.8% (Developing Very Well). This finding shows that loose part learning is effective in stimulating the creativity of early childhood and can be a strategy for stimulating the development of creativity at an early age, and can be an alternative innovation in learning that is fun and meaningful